Proceedings of the 2018 ACM International Conference on Interactive Experiences for TV and Online Video 2018
DOI: 10.1145/3210825.3210832
|View full text |Cite
|
Sign up to set email alerts
|

"I Can Watch What I Want"

Abstract: In recent years, on-demand video services, such as Netflix and Amazon Video, have become extremely popular. To understand how people use these services, we recruited 20 people from nine households to keep a viewing diary for 14 days. To better understand these household viewing diaries, in-depth interviews were conducted. We found that people took advantage of the freedom and choice that on-demand services offer, watching on different devices and in different locations, both in the home and outside. People oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
3
5
0
1
Order By: Relevance
“…We acknowledge that the sample size could be larger, but this project was very much intended to be an exploratory study. Furthermore, the sample size is in line with studies of a similar nature that investigate audience behavior, such as Radeta et al (2014), Mikos (2016), and Rigby et al (2018a). This also reflects the difficulty experienced in recruiting participants for this study, perhaps due to the requirement of installing logging software on participants’ computers, but also because the study took place on a small island with a low population.…”
Section: Limitations and Future Researchsupporting
confidence: 61%
See 1 more Smart Citation
“…We acknowledge that the sample size could be larger, but this project was very much intended to be an exploratory study. Furthermore, the sample size is in line with studies of a similar nature that investigate audience behavior, such as Radeta et al (2014), Mikos (2016), and Rigby et al (2018a). This also reflects the difficulty experienced in recruiting participants for this study, perhaps due to the requirement of installing logging software on participants’ computers, but also because the study took place on a small island with a low population.…”
Section: Limitations and Future Researchsupporting
confidence: 61%
“…The phenomenon of binge-watching must be understood, therefore, within the context of the digital era, during which many technologies have contributed to the emergence of new consumer behaviors with the potential for overuse (Flayelle et al, 2019). Netflix’s auto-play feature is an example of this, since it may make the interruption of a viewing session difficult (Jenner, 2018: 161; Rigby et al, 2018a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It also agrees with other studies examining the response to screen size on other measures, such as presence [25,33]. Furthermore, it is consistent with qualitative research on mobile viewing, where people often express a preference for larger screens [38]. Therefore, this result further validates the Film IEQ as an immersion measure -it is sensitive to the interventions that related measures are also sensitive to.…”
Section: Discussionsupporting
confidence: 89%
“…The variety of screen sizes in everyday computing is also present in the domain of video consumption. Rigby et al [38] found that the rise in popularity of on-demand video services meant that people are now watching Would you like to watch more of this, or similar content, in the future? 1 Table 2: Film IEQ questions, numbered by factor (1: captivation, 2: real-world dissociation, 3: comprehension, 4: transportation).…”
Section: Validation Experiment: the Effect Of Screen Size On Immersionmentioning
confidence: 99%
See 1 more Smart Citation